Correlation between kisspeptin and biochemical markers in obese and non-obese women with polycystic ovary syndrome - Meixiu Gao; Xinghua Tao; Qiong Zhang; Wenli He; Ting Zhao; Tao Yuan (Taylor & Francis Group, 2023)
Introduction The purpose of this study was to determine the association between kisspeptin levels and obesity in patients with polycystic ovary syndrome (PCOS) or in healthy controls and to explore the correlation between levels of kisspeptin and various endocrine and metabolic indices in each group.Methods From August 2020 to December 2021, the clinical data of 78 patients with polycystic ovary syndrome and 78 healthy individuals were collected. The two groups were further divided into obese and non-obese groups based on a BMI cutoff of 25. Serum kisspeptin levels were measured using enzyme linked immunosorbent assay (ELISA). Pearson's correlation analysis was used to determine the correlation between PCOS and kisspeptin levels.Results The weight, body mass index (BMI), and waist circumference (WC), estradiol (E2), and testosterone (T) of the obese PCOS group were significantly higher than those of the study group (p < .05). WC, kisspeptin, triglycerides (TG), glucose (GLU), alanine amiotransferase (ALT), blood urea nitrogen (BUN), uric acid (UA), E2, luteinizing hormone (LH), prolactin (PRL), and T in the non-obese PCOS group were higher than those in the control group, and the difference was statistically significant (p < .05). Levels of E2 and TG in the obese PCOS group were significantly higher than those in the non-obese PCOS group (p < .05). Kisspeptin levels in the PCOS group exhibited a significant positive correlation with LH, T, and AMH levels; kisspeptin level positively correlated with T in the non-obese PCOS group and with anti-Müllerian hormone (AMH) in the obese PCOS group.Conclusion Serum kisspeptin levels are associated with hormone levels in patients with PCOS. Kisspeptin correlates with distinct biochemical indices in obese versus non-obese groups, indicating that kisspeptin may play a role in the prognostication, treatment, and clinical evaluation of patients with varying BMI.